Orthodoxy versus post-communism?: Belarus, Serbia, Ukraine and the russkiy mir - Wawrzonek, Michał (Cambridge Scholars Publishing, 2016)
Orthodox Christianity vis-à-vis postcommunist transformation: a conceptual framework / Nelly Bekus and Michal Wawrzonek -- "Russkiy mir": a conceptual model of the "Orthodox civilization" / Michal Wawrzonek -- On the political mission of Orthodoxy in Belarus and its consequences for the church and state / Nelly Bekus -- The Serbian Orthodox Church facing the challenges of the post-Yugoslav space / Mirella Korzeniewska-Wiszniewska -- Orthodox Church and Orthodox tradition as the components of the political culture in Ukraine / Michał Wawrzonek